2
$\begingroup$

Note: Sorry, I posted this earlier with a glaringly obvious error - here's the improved version:

The statement I'm trying to prove is:

Let $ (x_n) $ be a convergent sequence and $ K \in \Bbb N $. Let $ (y_n) $ be the sequence defined by $ y_n = x_{n+K} $. Then $ (y_n) $ is also convergent and we have $ \lim_{n \to \infty}y_n=\lim_{n \to \infty}x_n. $

Proof:

Let $ \lim_{n \to \infty}x_n=x^* $. Since $(x_n)$ is convergent, by definition we have that given $\epsilon > 0 \quad \exists \quad N \in \Bbb N: \quad \left\lvert x_n - x^* \right\rvert < \epsilon \quad \forall \quad n \ge N$.

We know that $K \in \Bbb N $, therefore, $ n+K>N $. So we know for definite that $$ \left\lvert x_{n+K} - x^* \right\rvert < \epsilon \quad \implies \quad \left\lvert y_n - x^* \right\rvert < \epsilon$$

Hence, we can conclude that by definition of convergent sequences, $(y_n)$ is convergent with the limit $x^*$ which is also the limit of $(x_n)$ as $n \to \infty$. So the original statement is true. $\square$

Any confirmation of correctness/corrections would be greatly appreciated. Thank you.

$\endgroup$
1
  • $\begingroup$ Your proof seems to be correct. Basically, it´s just applying the definition of convergence. $\endgroup$
    – XPenguen
    Dec 22 '15 at 23:14
3
$\begingroup$

It’s basically correct, but you need to add a little more wording to make your reasoning entirely clear. When you state what it means for the original sequence to converge to $x^*$, you’re not actually picking an arbitrary $\epsilon$ and associated $N$: you’re just saying that for each $\epsilon>0$ there is an $N$ with a certain property. At that point you might continue something like this:

Now let $\epsilon>0$ be arbitrary, and let $N\in\Bbb N$ be such that $|x_n-x^*|<\epsilon$ whenever $n\ge N$. $K\in\Bbb N$, so $K\ge 0$, and therefore $n+K\ge n\ge N$ whenever $n\ge N$. In particular, this ensures that $|x_{n+K}-x^*|<\epsilon$ whenever $n\ge N$. Since $\epsilon>0$ was arbitrary, this implies that $\lim\limits_{n\to\infty}x_{n+K}=x^*$ as well.

$\endgroup$
0
$\begingroup$

You work is correct. Notice that every subsequences of a convergence sequence converges to the same limit. By formulates, If $(x_n)_n$ converges to $a$, then for every ascending strictly functions $\varphi: \mathbb{N} \rightarrow \mathbb{N}$, the sequences $(x_{\varphi(n)})_n$ is converges to $a$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.